NOTCH3 promotes malignant progression of bladder cancer by directly regulating SPP1 and activating PI3K/AKT pathway - Changxue Liu; Huaixi Ge; Chengquan Shen; Ding Hu; Xinzhao Zhao; Ruize Qin; Yonghua Wang (Cell Death and Disease)
Abstract The biological role and precise molecular mechanisms of Notch receptor 3 (NOTCH3) in the malignant progression of bladder cancer (BLCA) remain unclear. In this study, we found that NOTCH3 was significantly upregulated and associated with poor prognosis in BLCA patients. Functional experiments demonstrated that NOTCH3 knockdown inhibited BLCA cell proliferation, migration, invasion and significantly suppressed tumor growth and metastasis in vivo as well. Mechanically, chromatin immunoprecipitation and dual-luciferase reporter assays confirmed that NOTCH3 could promote the transcription of secreted phosphoprotein 1 (SPP1), a potential downstream target gene of NOTCH3, by binding to the CSL elements in the SPP1 promoter. Moreover, we also found that targeting NOTCH3 inhibited BLCA growth and metastasis by suppressing the SPP1-PI3K/AKT axis. Our study highlights the critical role of NOTCH3-SPP1-PI3K/AKT axis in the malignant progression of BLCA, suggesting that NOTCH3 may be a potential therapeutic target for BLCA.